2019
DOI: 10.1002/asia.201900990
|View full text |Cite
|
Sign up to set email alerts
|

Eutectic Molecular Liquids Based on Hydrogen Bonding and π–π Interaction for Exfoliating Two‐dimensional Materials and Recycling Polymers

Abstract: Eutectic molecular liquids (EMLs) based on hydrogen‐bonding interaction and π–π stacking were prepared. We found that the thermodynamic properties like initial decomposition temperature and glass transition temperature of EMLs are mainly dominated by the hydrogen bond donor, which is beneficial for designing and preparing new EMLs. These new liquid systems could be applied in the field of environmental and material science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 31 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…Therefore, it is necessary to propose a new type of DES. Moreover, the inverted DESs proposed in this work are not eutectic molecular liquids, because they are each composed of an ionic compound and a molecular compound, while the an eutectic molecular liquid is composed of two molecular compounds …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is necessary to propose a new type of DES. Moreover, the inverted DESs proposed in this work are not eutectic molecular liquids, because they are each composed of an ionic compound and a molecular compound, while the an eutectic molecular liquid is composed of two molecular compounds …”
Section: Figurementioning
confidence: 99%
“…Moreover,t he inverted DESs proposed in this work are not eutectic molecular liquids,b ecause they are each composed of an ionic compound and am olecular compound,w hile the an eutectic molecular liquid is composed of two molecular compounds. [11] 18-crown-6 ether is the most commonc rown ether,a nd the asymmetry of hostm olecules on melting point of DESs were also studied in this work. In addition, the molecular symmetry of benzo-15-crown-5 and benzo-18-crown-6 is similar,b ut the size of the main ring is different.…”
mentioning
confidence: 99%
“…DESs with high purity can be easily prepared by mixing hydrogen bond donors (HBDs) and hydrogen bond acceptors (HBAs), which may contain two or more constituents, and does not require further purification, therefore simplifying the processes. The interactions between the constituents can be hydrogen bonds, halogen bonds, or Pi-Pi interactions that cause the melting point of synthesized DES to be significantly reduced and lower than any of the individual component [20][21][22]. Abbott et al [23] reported the first example of DES through mixing choline chloride (ChCl) with urea (UE), and then Zhu et al [24] reported that ChCl:UE DES can effectively catalyze the reactions of CO 2 and epoxides.…”
Section: Introductionmentioning
confidence: 99%
“…In literature, hydrogen bonding interaction between the DES components was considered usually responsible to form a DES. However, Yu and co‐workers proposed that π‐ π bonding, host–guest interaction, and halogen bonding are other possible mode of interactions between the DES components (Yu et al, 2019; Yu et al, 2019; Yu & Mu, 2019). Therefore, depending on the mode of interaction, the DES components can also be named as electron donor and electron acceptor in addition to HBA and HBD.…”
Section: Introductionmentioning
confidence: 99%